Impairment of corneal epithelial wound healing is association with increased neutrophil infiltration and reactive oxygen species activation in tenascin X-deficient mice - Sumioka, Takayoshi (Lab Invest, 2021)
The purpose of the study was to uncover the role of tenascin X in modulation of healing in mouse corneas subjected to epithelium debridement. Healing in corneas with an epithelial defect was evaluated at the levels of gene and protein expression. Wound healing-related mediators and inflammatory cell infiltration were detected by histology, immunohistochemistry and real-time RT-PCR. Tenascin X protein was upregulated in the wounded wild-type (WT) corneal epithelium. The lack of tenascin X impaired closure of an epithelial defect and accelerated infiltration of neutrophils into the wound periphery as compared to the response in WT tissue. Expression of wound healing-related proinflammatory and reparative components, i.e., interleukin-6, transforming growth factor β, matrix metalloproteinases, were unaffected by the loss of tenascin X expression. Marked accumulation of malondialdehyde (a lipid peroxidation-derived product) was observed in KO healing epithelia as compared with its WT counterpart. Neutropenia induced by systemic administration of a specific antibody rescued the impairment of epithelial healing in KO corneas, with reduction of malondialdehyde levels in the epithelial cells. Finally, we showed that a chemical scavenging reactive oxygen species reversed the impairment of attenuation of epithelial repair with a reduction of tissue levels of malondialdehyde. In conclusion, loss of tenascin X prolonged corneal epithelial wound healing and increased neutrophilic inflammatory response to debridement in mice. Tenascin X contributes to the control of neutrophil infiltration needed to support the regenerative response to injury and prevent the oxidative stress mediators from rising to cytotoxic levels.